Pemanfaatan Aplikasi Siwaslu 1.1.0 pada Pengawasan Kegiatan Pemilu 2024 di TPS 85 Kelurahan Binjai Kecamatan Medan Denai - Gultom, Pesta (Universitas Methodist Indonesia, 2024)
The 2024 Simultaneous General Election will take place on Wednesday, February 14 2024. On the same day, the President and Vice President (Pilpres) elections will be held simultaneously, as well as the Legislative Election (Pileg) to elect members of the DPD RI, DPR RI, members of the Provincial DPRD, and elect Regency/City DPRD members. The implementation of supervision at TPS 85 Binjai Subdistrict, which was carried out directly, was carried out well and smoothly. and is carried out in 5 stages, where stage 1: Monitoring quiet days. stage 2: Supervision of voting preparations, stage 3: Supervision of voting implementation, stage 4: Supervision of counting ballot papers, and stage 5: Supervision of the recording of vote counts, and distribution of ballot boxes from TPS 85 to the Binjai Village Election Committee, Supervision results reporting system which was carried out by the Supervisor of TPS 85 Binjai Village using Google Form and the SIWASLU application version 1.1.0.